Satisfaction and Its Relationship with Loyalty in Ecotourism: A Study in Costa Rica - CARVACHE-FRANCO, Mauricio; CARVACHE-FRANCO, Wilmer; VÍQUEZ-PANIAGUA, Ana Gabriela; CARVACHE-FRANCO, Orly; PEREZ-OROZCO, Allan (Journal of Environmental Management and Tourism; Vol 12 No 3 (2021): JEMT Volume XII Issue 3(51) Summer 2021, 2021)
Within ecotourism, the service can be improved with proper planning, achieving greater satisfaction and return of tourists, benefiting the destination and the community with higher income and employment. The objectives of this study were a) to analyze the relationships between tourists’ general satisfaction and loyalty, and b) to analyze the influence that the service aspects exert on the satisfaction and return of tourists. The study was conducted in Costa Rica, a Central American country with great ecological wealth for ecotourism. Three hundred ten questionnaires were filled out in the Arenal National Park and the Caño Negro National Wildlife Refuge. Spearman's statistical method of correlation was used for data analysis. As main results, the aspects of the service had a significant and positive influence on the satisfaction and return intentions of tourists. The aspects that most influenced general satisfaction were accessibility and infrastructure, tranquility, gastronomic quality, and the human treatment received. While the aspects that most influenced the return intentions were the tourist information and signage, the gastronomic quality, the accessibility of the infrastructure, and the equipment and facilities of the restaurant. The findings will serve to develop sustainable plans in protected areas and to improve service in ecotourism.